The Impact of Natural Disasters on Smallholders - Mulono Apriyanto; KMS Novyar Satriawan Fikri; Marlina Marlina; Ali Azhar (Akademi Komunitas Perkebunan Yogyakarta, 2023)
Specifically, the purpose of this paper is to discuss the impact of natural disasters on food security in smallholders. Data sources and information are gathered from research findings, journals, and relevant articles, and then descriptively analyzed in order to ensure that they are consistent with the purpose of this article